Evaluation of Quality of Life, Depression and Anxiety in Patients with Rectal Cancer Receiving Radiotherapy - Feryal Karaca; Selahattin Menteş; Yaşar Sertdemir (Van Tıp Dergisi, 2020)
INTRODUCTION: Rectal cancers (RC) constitute one third of colorectal cancers. Chemoradiotherapy (CRT) is the standard treatment of locally advanced stage RC. European Organization for Research and Treatment of Cancer Quality of Life Questionnairer (EORTC-QLQ C30) is a quality of life scale and that is highly valid and reliable all over the world. State-Trait Anxiety Inventory (STAI) is an anxiety scoring questionnaire is examined in two forms; STAI1 (statefulness) and STAI2 (continuity). The Beck Depression Inventory measures depression symptoms. The aim of this study was to compare the quality of life, anxiety and depression of patients before and after radiotherapy (RT0) and after radiotherapy (RT1). METHODS: EORTC-QLQ C30, STAI1, STAI2 and Beck depression questionnaires were applied to 32 patients who applied to our clinic with the diagnosis of RC between November 2016-August 2019. RESULTS: Social function score, dyspnea which are compared at RT0 and RT1 times; was not statistically significant p> 0.05, borderline pain score was found to be significant p = 0.067 and the other quality of life scores were statistically significant p<0.05. STAI2 and Beck test were statistically significant p <0.05 which are compared at RT0 and RT1 times, STAI1 test was not statistically significant p> 0.05. DISCUSSION AND CONCLUSION: Based on these results, quality of life, anxiety and depression of the patients with RC should be closely controlled during RT.